The Effect of Job Placement and Training on the Work Productivity of Employees in the Central Preparation Production Section at PT Adis Dimension Footwear, Tangerang Regency - Ratnasari, Ratnasari; Yulandari, Sri; Putra, Awang Darmawan (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine partially or simultaneously the effect of job placement and job training on the work productivity of employees in the Central Preparation Production section at PT. Adis Dimension Footwear, Tangerang Regency. This study uses a quantitative descriptive method. The research sample consisted of 78 respondents. The results of this study indicate that partially and simultaneously, job placement and training significantly affect the work productivity of employees in the Central Preparation Production section at PT. Adis Dimension Footwear, Tangerang Regency. This finding indicates the importance of job placement and training in the company, because it will greatly determine whether or not the employee is suitable for the work given by the company.